Listen, look & learn: Exploring cultural obligations of Elders and older Aboriginal people. Issue 2 (2nd April 2020) - Gibson, Chontel; Dudgeon, Pat; Crockett, Judith
ABSTRACT: Introduction: Aboriginal and Torres Strait Islanders' social and emotional well-being provides a strength-based framework to discuss social and emotional well-being. This paper focuses on Elders' and older Aboriginal people's experiences of social and emotional well-being and their cultural obligations relating to social and emotional well-being. These cultural obligations, along with social and emotional well-being experiences, inform and/or are influenced by Elders and older people's occupations. Methods: An Indigenous Standpoint Theory guided this research and supported yarning as a research method. In total, 16 older Aboriginal people participated in this research. A modified version of an existing thematic analysis process was used to organise the data, which enabled research yarning members to participate and engage in all stages of data analysis. Results: Three key themes were identified: 1). Every day you will learn something; 2). It all comes back to culture; 3). The old wings, they used to be flyin', are just lying beside them. These themes highlight the importance of older Aboriginal people participating in learning activities and fulfilling cultural obligations that support social and emotional well-being. Factors like disrespect, poor health and/or well-being, broken cultural connections, and geography negatively influence participation in roles, responsibilities, and occupations. Conclusion: Elders and older people are integral in maintaining the cultural well-being of family, community, and country. This social and emotional well-being framework provides a respectful foundation to discuss Elders' and older Aboriginal people's cultural obligations, with the cultural domain providing a solid foundation for exploring Elders' and older people's occupations.